Statistical analysis of network data flows and predictions using statistical and machine learning regression models - Boateng, Albert; Rahim, Maheen Mehjabeen (Brac University, 2024)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Mathematics 2024.